Unity Behind Diversity or the Reverse? The Language of Universality in Amma and Bhagavan’s Oneness Movement - Thorsén, Elin (International Journal for the Study of New Religions, 2016)
This article addresses how a language and practice of non-denominational universality is used within the Oneness movement, and the ways in which this universality has been crucial in order to appeal to a global audience. The Oneness movement, founded by the couple Sri Amma and Bhagavan, originated in South India in the 1990s, and has gained a substantial international following during the last decade. The cornerstone of the movement is the practice of giving and receiving deeksha, a kind of energy transmission said to usher the receiver into a state of higher consciousness. Drawing on empirical material collected during fieldwork with Oneness groups in India and Sweden, and taking the concepts of portable practice and transposable message as a point of departure, the practice of deeksha and the message of an all-encompassing human potential for spiritual awakening is analysed in order to find the themes that have made Oneness appealing in a global context. It is argued that the diffusion of Oneness into new cultures has been a balancing act between on the one hand adaptation to local cultures, and on the other hand claims of universal applicability and validity. By making use of the argument that their spiritual message stretches beyond boundaries such as those imposed by culture and religion, the Oneness movement sees its message as compatible with most (if not all) major religious traditions, and can thus encourage cultural adaptation of their teachings without loosing their credibility. This makes the language of universality function as an important strategy in the process of acquiring legitimacy on a global level.